ANALYSYS OF TEACHER QUESTIONING SKILLS: THE USE OF OPEN-ENDED QUESTIONS IN LEARNING - Kurniawati, Kurniawati (JMIE (Journal of Madrasah Ibtidaiyah Education), 2023)
This study aims to analyze teacher questioning activities using oral open-ended questions in class This study involved three elementary school teachers from two different schools in Yogyakarta. Samples are selected using convenience sampling techniques. The data collection technique used was two learning observations lasting 45-60 minutes using zoom meeting recordings and google meet. Records and transcripts of recordings were analyzed to find answers to three research questions. The results showed that teachers asked all kinds of questions verbally. The teacher asked two or three open-ended questions verbally. Students answer these questions with different answers. The answer is not only correct, but also false and incomplete. After getting an answer, the teacher responds by asking follow-up questions both closed and open-ended. Therefore, this study helped teachers to know the usefulness of oral open-ended questions, to understand how to optimize asking the questions orally, and to analyze the use of oral open-ended questions in the classroom. Researchers can also reflect on the way to do study related to questioning activity in which they are expected to focus on all the types of questions, the way teachers ask, students possible answers, and follow-up the answer.